PIPE investments of private equity funds : the temptation of public equity investments to private equity firms - Särve, Bernhard (Reihe Alternative Investment, 2013)
Usually, private equity firms take control of firms which are privately held, and tend to act hidden. But, in recent years, the rising phenomenon of private investments in publicly listed companies, so-called PIPEs, could be observed. At first, this seems to be inconsistent but, it could become a perfect way to generate good returns. This book gives an overview about the PIPE market, and then focuses on the role of private equity funds. How do they invest in publicly listed firms? And what are their motivations? Is the overall performance of PIPE deals superior to those of traditional priv.